STUDENT AGENCY IN CLASSROOM: AN OVERVIEW - Tiwari, Anjali (ShodhKosh: Journal of Visual and Performing Arts, 2023)
In majority of schools, we see learners who are usually marked as errant, non-conforming and rule breaking. We try to understand them from the viewpoint of school, which may be termed as an ‘outsider view’ because, in such areas we never give space to the voices of learners. But there is need to explore this from an ‘insider view’, i.e. understanding, their behaviour from their own viewpoint. This is termed as ‘student agency’ in academic literature. In this research paper, the researcher has tried to interpret and understand student’s agency in two different ways. One genera try to explain about the reasons and features of student agency and see it in the form of subcultural groupings and other genera move a step forward from causes and features of student agency and try to find other nuances of this and see it as a resource for creating democratic teaching learning environment.